2014
DOI: 10.5114/kitp.2014.47337
|View full text |Cite
|
Sign up to set email alerts
|

CARDIAC SURGERY Use of bone wax is related to increased postoperative sternal dehiscence

Abstract: AimTo investigate the relation between use of bone wax and postoperative sternal dehiscence after cardiac surgery.Material and methodsFive thousnad three hundred and eighteen consecutive patients who underwent cardiac surgery between 1999 and 2009 were evaluated prospectively. Perioperative use of bone wax, perioperative data and outcome parameters were recorded. Multivariate logistic regression analysis was performed to define independent risk factors for postoperative sternal dehiscence.ResultsBone wax was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…For the HP arm of the study, there was only one AE of sternal dehiscence (1 of 83 cardiothoracic patients [1.2%]) which was not attributed to the use of HP by the investigator and the CEC. In a 10‐year prospective observational study, Alhan et al found sternal dehiscence to be attributable to the use of bone wax in 2.4% of cardiac cases in which it was used . No instances of sternal non‐union were reported in patients treated with HP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the HP arm of the study, there was only one AE of sternal dehiscence (1 of 83 cardiothoracic patients [1.2%]) which was not attributed to the use of HP by the investigator and the CEC. In a 10‐year prospective observational study, Alhan et al found sternal dehiscence to be attributable to the use of bone wax in 2.4% of cardiac cases in which it was used . No instances of sternal non‐union were reported in patients treated with HP.…”
Section: Discussionmentioning
confidence: 99%
“…G + T was selected as the control agent for several reasons. G + T is one of the most frequently used hemostatic agents in the United States . The components of the control article are very similar to those of the investigational device (porcine gelatin with recombinant human thrombin vs. porcine collagen with human pooled plasma thrombin, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The reaction is characterized by giant cells, plasma cells, fibrous tissue, and a lack of bone formation, which eventually may trigger an allergic reaction or granuloma formation. 5 This histologically is seen in the two cases described above. In vivo studies have demonstrated that bone wax also delays wound-healing by inhibiting osteogenesis, 3 and it induces inflammation by affecting bacterial clearance in cancellous bone.…”
Section: Discussionmentioning
confidence: 71%
“…Granuloma formation and foreign body reaction from bone wax have been described in the orbit, nasal cavity, mastoid, cerebellopontine angle, and foot. The reaction is characterized by giant cells, plasma cells, fibrous tissue, and a lack of bone formation, which eventually may trigger an allergic reaction or granuloma formation . This histologically is seen in the two cases described above.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation